Eculizumab in refractory generalized myasthenia gravis previously treated with rituximab: subgroup analysis of REGAIN and its extension study. Issue 6 (14th October 2021) - Siddiqi, Zaeem A.; Nowak, Richard J.; Mozaffar, Tahseen; O'Brien, Fanny; Yountz, Marcus; Patti, Francesco; ,
Abstract: Introduction/Aims: Individuals with refractory generalized myasthenia gravis (gMG) who have a history of rituximab use and experience persistent symptoms represent a population with unmet treatment needs. The aim of this analysis was to evaluate the efficacy and safety of eculizumab in patients with refractory anti‐acetylcholine receptor antibody‐positive (AChR + ) gMG previously treated with rituximab. Methods: This post hoc subgroup analysis of the phase 3 REGAIN study (NCT01997229) and its open‐label extension (OLE; NCT02301624) compared baseline characteristics, safety, and response to eculizumab in participants who had previously received rituximab with those who had not. Rituximab use was not permitted within the 6 months before screening or during REGAIN/OLE. Results: Of 125 REGAIN participants, 14 had received rituximab previously (7 received placebo and 7 received eculizumab). In the previous‐rituximab group, 57% had used at least four other immunosuppressants compared with 16% in the no‐previous‐rituximab group. Myasthenia Gravis Activities of Daily Living total scores from eculizumab baseline to week 130 of eculizumab treatment improved in both the previous‐rituximab and no‐previous‐rituximab groups (least‐squares mean −4.4, standard error of the mean [SEM] 1.0 [n = 9] and least‐squares mean −4.6, SEM 0.3 [n = 67], respectively; difference = 0.2, 95% confidence interval −1.88 to 2.22). In addition, in both groups, most patients who were treated with eculizumab for 130 weeks achieved a Myasthenia Gravis Foundation of America post‐intervention status of minimal manifestations (66.7% and 65.0%, respectively). The eculizumab safety profile was similar between groups and consistent with its established profile. Discussion: Eculizumab is an effective therapy for patients with refractory AChR + gMG, irrespective of whether they had received rituximab treatment previously.